Current trends in altitude training - Wilber, R. L. (Sports Medicine, 2001)
Recently, endurance athletes have used several novel approaches and modalities for altitude training including: (i) normobaric hypoxia via nitrogen dilution (hypoxic apartment); (ii) supplemental oxygen; (iii) hypoxic sleeping devices; and (iv) intermittent hypoxic exposure (IHE). A normobaric hypoxic apartment simulates an altitude environment equivalent to approximately 2000 to 3000m (6560 to 9840ft). Athletes who use a hypoxic apartment typically 'live and sleep high' in the hypoxic apartment for 8 to 18 hours a day, but complete their training at sea level, or approximate sea level conditions. Several studies suggest that using a hypoxic apartment in this manner produces beneficial changes in serum erythropoietin (EPO) levels, reticulocyte count and red blood cell (RBC) mass, which in turn may lead to improvements in postaltitude endurance performance. However, other studies failed to demonstrate significant changes in haematological indices as a result of using a hypoxic apartment. These discrepancies may be caused by differences in methodology, the hypoxic stimulus that athletes were exposed to and/or the training status of the athletes. Supplemental oxygen is used to simulate either normoxic (sea level) or hyperoxic conditions during high-intensity workouts at altitude. This method is a modification of the 'high-low' strategy, since athletes live in a natural terrestrial altitude environment but train at 'sea level' with the aid of supplemental oxygen. Limited data regarding the efficacy of hyperoxic training suggests that high-intensity workouts at moderate altitude (1860m/6100ft) and endurance perfor- mance at sea level may be enhanced when supplemental oxygen training is utilised at altitude over a duration of several weeks. Hypoxic sleeping devices include the Colorado Altitude Training (CAT) Hatch (hypobaric chamber) and Hypoxico Tent System (normobaric hypoxic system), both of which are designed to allow athletes to sleep high and train low. These devices simulate altitudes up to approximately 4575 m/15006 ft and 4270 m/14005 ft, respectively. Currently, no studies have been published on the efficacy of these devices on RBC production, maximal oxygen uptake and/or performance in elite athletes. IHE is based on the assumption that brief exposures to hypoxia (1.5 to 2.0 hours) are sufficient to stimulate the release of EPO, and ultimately bring about an increase in RBC concentration. Athletes typically use IHE while at rest, or in conjunction with a training session. Data regarding the effect of IHE on haematological indices and athletic performance are minimal and inconclusive.